Mass Optimization of Acid-Activated and Acid-Thermal-Activated Bentonite in Heavy Metal Adsorption - Jilan Nafisah Koenang; Tuty Emilia Agustina; Tine Aprianti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Heavy metal pollution such as Cu, Fe, and Pb is a serious environmental issue because it is toxic and can harm living things and the surrounding environment. Adsorption is a potential method to address heavy metal problems with bentonite as an adsorbent. Before use, natural bentonite will be activated first. Activation aims to increase the surface area, porosity, and number of active sites on the bentonite surface. This study aims to determine the optimum adsorbent mass in heavy metal adsorption and compare the best activation method using acid-activated bentonite (H₂SO₄ 1.2M) and acid-thermal activated bentonite, namely H₂SO₄ 1.2M and continued heating using a 300ᵒC furnace for 6 hours. In addition, comparing changes in the surface characteristics of acid bentonite and acid-thermal bentonite through characterization using SEM analysis. Adsorption was carried out using a single component synthetic solution containing Cu, Fe, and Pb metals with variations in adsorbent mass of 1, 2, 3, 4, and 5 grams. The results show that acid bentonite has an open and porous surface structure and has many active sites. In acid-thermal bentonite, the silicate structure becomes more stable despite slight damage to the Si structure and at a higher mass makes acid-thermal bentonite higher than acid bentonite. The optimum heavy metal degradation efficiency is achieved at an adsorbent mass of 1 gram with acid-activated bentonite which achieves a metal degradation efficiency of 45% Cu, 100% Fe and 88%.